2018
DOI: 10.3390/dj6040072
|View full text |Cite
|
Sign up to set email alerts
|

Commitment of Oral-Derived Stem Cells in Dental and Maxillofacial Applications

Abstract: Tissue engineering is based on the interaction between stem cells, biomaterials and factors delivered in biological niches. Oral tissues have been found to be rich in stem cells from different sources: Stem cells from oral cavity are easily harvestable and have shown a great plasticity towards the main lineages, specifically towards bone tissues. Dental pulp stem cells (DPSCs) are the most investigated mesenchymal stem cells (MSCs) from dental tissues, however, the oral cavity hosts several other stem cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 37 publications
3
77
0
Order By: Relevance
“…SCAPs were categorized as multipotent mesenchymal stem cells (MSCs) after a positive expression of STRO-1, CD146, CD73, CD90, and CD105 markers. [4][5][6]. It has been suggested that MSCs may be present virtually in any vascularized tissue [7], so the expression of the aforementioned markers, indicative of MSC nature, reflect the perivascular location and multilineage differentiation potential of SCAPs [8].…”
Section: Introductionmentioning
confidence: 99%
“…SCAPs were categorized as multipotent mesenchymal stem cells (MSCs) after a positive expression of STRO-1, CD146, CD73, CD90, and CD105 markers. [4][5][6]. It has been suggested that MSCs may be present virtually in any vascularized tissue [7], so the expression of the aforementioned markers, indicative of MSC nature, reflect the perivascular location and multilineage differentiation potential of SCAPs [8].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the treatment, the material is placed in the root-end cavity sealing the entire area [3][4][5]. This area is where the stem cells from the periodontal ligament (PDLSCs) are located and are in direct contact with the retrograde root filling material [6,7]. The interaction between the PDLSCs and the material should improve the regeneration of the area; several studies have proven that it favors the healing of the cementum, alveolar bone, gingiva, and periodontal ligament [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, stem cell-based bone tissue engineering offers a promising strategy for alveolar bone regeneration (27). Oral tissues that are rich in stem cells have been thought as important sources in regenerative medicine (28). The capsules of DC initially originate from the odontogenic epithelium in the embryonic period, which means it is likely that naive cells hide in them.…”
Section: Discussionmentioning
confidence: 99%